Local Government Policies in Increasing the Human Development Index in Bone District - M Awaluddin; Muhammad Asdar; Rusnaedi Rusnaedi; Hasnah Bolkiah; Novi Firman; Erviandy Samir (Universitas Negeri Makassar, 2021)
HDI is an indicator used to see development progress in the long term. The purpose of this study is to see and analyze how effective the policies are to increase the Human Development Index in Bone Regency by the Bone Regency government and then to provide alternative policy recommendations to the Bone Regency regional government. The type of research method used by the researcher is the descriptive qualitative research method. The research was conducted at the BAPPEDA office in Bone Regency. The data sources used are primary and secondary data. The results of this study indicate that the Policy Context is deemed to have been by the problems being faced. existing policies contain things that can solve the problem to be solved. However, in its implementation, the indicators for the preparation of HDI in Bone Regency are still lagging behind other regencies/cities in South Sulawesi, Bone Regency's HDI is still ranked 23rd out of 24 city districts. but the increase is not as big and fast as other districts. Therefore, the Bone Regency government feels it is necessary to evaluate the implementation of the policies that have been issued.